Mirror-reading and writing in association with right-left spatial disorientation. - Heilman, K M (1980)
A left-handed patient suddenly developed a right hemiparesis, mirror-reading, and mirror-writing. Although he could discriminate between right and left on himself, he demonstrated right/left spatial disorientation. We propose that his right/left spatial disorientation was induced by a scanning defect. It has been demonstrated that mirror-image engrams are normally available. We believe that a reversal of the learned left-to-right scanning process with the availability of mirror engrams induced mirror-reading. Similarly, reversal of the normal left-to-right writing pattern, with the availability of mirror engrams, induced mirror-writing.